Interwar U.K. unemployment: the Benjamin and Kochin hypothesis or the legacy of "just" taxes? - James M. Nason; Shaun P. Vahey (Federal Reserve Bank of Atlanta, 2006)
Benjamin and Kochin (1979, Journal of Political Economy) present regression estimates to support their hypothesis that larger unemployment benefits increased U.K. unemployment post–World War I (WWI). The Benjamin-Kochin (BK) regression is easy to replicate. When the replication is widened to include income tax rates and WWI observations using Bayesian Monte Carlo methods, the evidence moves against the BK hypothesis and in favor of regressions that include the capital income tax rate. We explain these results with Daunton (2002, Just Taxes). He argues that U.K. tax rates were set during WWI and the interwar period to achieve an equitable, or "just," mix of taxes and debt. Neoclassical theory suggests that capital income tax rates fluctuations created inefficient factor input allocations that drove up interwar U.K. unemployment.
Keywords: 330; Arbeitslosigkeit; Arbeitslosenversicherung; Kapitalertragsteuer; Markovscher Prozess; Großbritannien